Improving professional training of pre-service math teachers on the basis of massive open online courses - V. V. Pikalova (CTE Workshop Proceedings, 2015)
Research goal: to analyze the content and structure of instructivist massive open online courses of mathematics and computer sciences (MOOC) offered by some leading universities and based on the platforms Udacity, Coursers and edX. Research objectives: to determine the main directions of using MOOC in the professional training of pre-service math teachers within the educational context of the pedagogical college. Object of research: professional training of pre-service math teachers. Subject of research: professional training of pre-service math teachers on the basis of massive open online courses. Research methods used: analysis of statistics and publications. Results of the research. The most useful courses have been singled out to be further offered for students and teachers of natural science and mathematics. The benefits and shortcoming of the analyzed courses have been weighed up. The experiment on practical application of MOOC in teaching and learning process of the 4-th and 5-th year students was conducted and the results are presented. Recommendations for the implementation of MOOC into the educational process have been formulated. The main conclusions and recommendations: MOOC appropriate to include support for the teaching of certain subjects; improving methods MOOC introduction in the educational process should be accompanied by retraining teachers to the development of existing and new courses.